Implementasi Penguatan Profil Pelajar Pancasila dalam Pembelajaran Mengonstruksi Teks Eksplanasi dengan Model Problem Based Learning di Kelas XI SMAN 1 Parongpong - Regita Widiyanti; R.Panca Pertiwi Hidayati; Rendy Triandy (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This research is motivated by the low ability of students in writing, especially writing explanatory texts. This is caused by students who feel they have no talent and are unable to express their creativity in writing, as well as the lack of effectiveness of the learning model used by educators. One learning model that can foster student creativity is the problem-based learning model. The purpose of this study was to find out: the ability of the writer to implement the Pancasila Student Profile in the module in the implementation and assessment of learning to construct explanatory text using the problem based learning model of students in class XI SMAN 1 Parongpong, to describe the ability of students to implement Pancasila Student Profiles in constructing explanatory texts based on the type and elements of making explanatory text; and describe the ability of students to implement explanatory texts on Pancasila Student Profiles in the arrangement of explanatory texts using the problem based learning model. This research uses quantitative methods. This study presents the learning outcomes of writing explanatory texts on students' critical reasoning abilities based on the types and elements of making explanatory texts using the problem based learning model. It is evident from the results of the average pretest of experimental class students getting 53.30 while the acquisition of an average post-test score of 93,75indicates an increase in grades.